Percutaneous Coronary Intervention of Saphenous Vein Graft in Post-CABG Patients- Experience at a Tertiary Cardiac Centre (Bangladesh Heart Journal, 2020)
Background: Percutaneous Coronary Intervention (PCI) of obstructed & atheromatous venous graft is a real challenge for interventionist to deal with as SVG PCI patients are usually older with significant coronary & non coronary comorbidities. SVG usually presents a degenerated pattern of atherosclerosis with complex friable thrombosis prone lesions, higher risk of distal embolization, poorer long-term outcome with higher ISR rateObjectives: In the current era, with the advent and availability of different Drug Eluting Stents, PCI of SVG vessel is an alternative to re-do surgery for the occlusion of graft vessel. Although, PCI is associated with higher risk of instent restenosis, target vessel repeat revascularization, myocardial infarction or death. Uses of embolic protection devices is class I indication by ACC/AHA for SVG PCI. Therefore, we have carried out this prospective study, to see the outcomes of SVG vessel PCI at our center.Methods and materials: Patients were enrolled in this observational non-randomized prospective cohort, who underwent routine CAG for the post CABG angina, shortness of breath, dyspnea on minimal exertion or hospital admission with MI, NSTEMI, Angina II-III and planned for PCI of occluded graft vessel. Total 50 patients were enrolled in this study. Distal protection devices were not used in most of the cases as financial costing is an issue.Results:Total 46 patients were enrolled in this observational study. Average age of the patient population was (62.1±10.8), female 3(6.5%): male 43(93.5%), BMI (24.9±2.9). Among the CAD risk factors; DM 30(60%), HTN 34(68%), Dyslipidemia 31(62%), Smoking 12(6%) And family history of IHD 9(18%). Graft vessel occlusion occurred average (11.5+5.4 Yrs.) after CABG. SVG to OM is the commonest vessel, that developed significant stenosis in 27(56%), followed by LAD 9(16.1%), RCA 6(10.7%), PDA 6(10.7%), PLB 3(5.4%), DG 3(5.4%)m and LIMA-LAD 1(1.8%). Total 63 stents were deployed in 56 vessels of 46 patients. Double or overlapping stents were deployed; two stents in 11 (17.5%) and three stents in 1 (2%) vessel. One patient had recurrent ISR of SVG-OM stents and had PCI at our center and elsewhere. Common DES were, Sirolimus 25(39.7%), Everolimus 22(34.9%), BMS 9(14.3%), Zotarolimus 3 (4.8%). Average stent size was 3.3mm in Diameter. Total 3 (6%) patient died, in 1 month to 2yrs after the procedure. No acute or late complications were noted in this small group of patients and all were doing well at 12-24 months OPD follow-up.Conclusion: We found that our patients developed graft vessel occlusion on an average 11yrs, after CABG. OM is the commonest territory to develope significant stenosis. PCI of SVG survival outcome was 93.5% (43 patient) in this very primitive observational cohort and all were doing well with OPD follow-up. Thus, we recommend percutaneous coronary intervention of occluded or stenosed graft vessel as an alternative to re-do surgery in this part of the world.Bangladesh Heart Journal 2020; 35(1) : 6-13